Value of HIV patients with regular follow‐up as In‐house Internal Controls of Flow Cytometry Measurement of Lymphocyte Subsets. Issue 5 (8th August 2013) - de Carvalho Bittencourt, Marcelo; Kohler, Chantal; Henard, Sandrine; Rabaud, Christian; Béné, Marie C.; Faure, Gilbert C.
Abstract : Background: Quality assessment in flow cytometry cannot obey the same rules as those applicable to the measurement of chemical analytes. However, regular follow‐up of known patients may provide a robust in‐house control of cell subsets evaluation. Methods: Sequential blood samples assessed for 32 HIV patients over several years and showing good stability were retrospectively assessed to establish coefficient of variations of the percentages of CD3+, CD4+, CD8+ cells, and CD4+ absolute counts (ACs). Results: Mean relative standard variations for the whole cohort were of 0.04, 0.14, 0.08, and 0.18 for CD3%, CD4%, CD8%, and CD4 ACs, respectively. Discussion: In‐house follow‐up of regularly checked compliant patients is a good alternative to traditional and costly repeatability and reproducibility studies for the validation of routine flow cytometry. © 2013 International Clinical Cytometry Society